Light-related Loci Controlling Seed Germination in Ler × Cvi and Bay-0 × Sha Recombinant Inbred-line Populations of Arabidopsis thaliana - Laserna, María Paula (Oxford University Press, 2008)
BACKGROUND AND AIMS: Dormancy is a complex trait finely regulated by hormones and environmental factors. The phytochromes that sense red:far-red (R:FR) are the sole photoreceptors involved in the termination of dormancy and the induction of germination by light. The aims of this study were to identify and characterize loci controlling this process in seeds of Arabidopsis thaliana. METHODS: Recombinant inbred lines (RILs) derived from Landsberg erecta and Cape Verde Islands (Ler × Cvi), and Bayreuth and Shahdara (Bay-0 × Sha) were used to map loci related to light effects in seeds previously exposed to chilling and after-ripening periods. KEY RESULTS: Substantial genetic variation was found between accessions of A. thaliana in the induction of germination by light. Twelve loci were identified under R, FR or darkness, some of which were novel loci: DOG8, DOG9, DOG13, DOG14 and DOG15 detected in the Ler × Cvi RIL population; and DOG10, DOG11 and DOG12 mapped in the Bay-0 × Sha RIL population. Furthermore, independent loci were mapped for the induction of germination by low fluence (DOG-LF1 and DOG-LF2) and very low fluence of light (DOG-VLF1) in the Ler × Cvi RIL population. Several loci were confirmed and characterized after different after-ripening and chilling treatments through near-isogenic lines (NILs) and heterogeneous inbred families (HIFs). CONCLUSIONS: The results show that one group of loci act in a wide range of environmental scenarios, whereas a smaller group of loci are relevant only under a narrower set of conditions when the influence of the most-prevalent loci is reduced as a consequence of changes in the physiological status of the seeds. In addition, the identification of specific loci controlling the action modes of the phytochromes improves our understanding of the two independent signalling pathways that promote germination in response to light.